Effects of high-definition transcranial direct current stimulation on the cortical−muscular functional coupling and muscular activities of ankle dorsi−plantarflexion under running-induced fatigue - Zhan, Jianglong; Yu, Changxiao; Xiao, Songlin; Shen, Bin; Zhang, Chuyi; Zhou, Junhong; Fu, Weijie (Frontiers in Physiology, 2023)
Transcranial direct current stimulation (tDCS) can improve motor control performance under fatigue. However, the influences of tDCS on factors contributing to motor control (e.g., cortical−muscular functional coupling, CMFC) are unclear. This double-blinded and randomized study examined the effects of high-definition tDCS (HD-tDCS) on muscular activities of dorsiflexors and plantarflexors and CMFC when performing ankle dorsi–plantarflexion under fatigue. Twenty-four male adults were randomly assigned to receive five sessions of 20-min HD-tDCS targeting primary motor cortex (M1) or sham stimulation. Three days before and 1 day after the intervention, participants completed ankle dorsi–plantarflexion under fatigue induced by prolonged running exercise. During the task, electroencephalography (EEG) of M1 (e.g., C1, Cz) and surface electromyography (sEMG) of several muscles (e.g., tibialis anterior [TA]) were recorded synchronously. The corticomuscular coherence (CMC), root mean square (RMS) of sEMG, blood lactate, and maximal voluntary isometric contraction (MVC) of ankle dorsiflexors and plantarflexors were obtained. Before stimulation, greater beta- and gamma-band CMC between M1 and TA were significantly associated with greater RMS of TA (r = 0.460–0.619, p = 0.001–0.024). The beta- and gamma-band CMC of C1-TA and Cz-TA, and RMS of TA and MVC torque of dorsiflexors were significantly higher after HD-tDCS than those at pre-intervention in the HD-tDCS group and post-intervention in the control group (p = 0.002–0.046). However, the HD-tDCS-induced changes in CMC and muscle activities were not significantly associated (r = 0.050–0.128, p = 0.693–0.878). HD-tDCS applied over M1 can enhance the muscular activities of ankle dorsiflexion under fatigue and related CMFC.